Missionaries, Anthropologists and Cultural Change [Part I]. Studies in Third World Societies. (2022)
eng: The topics of anthropologist-missionary relationships, theology and missiology, research methods and missionary contributions to ethnology, and missionary training and methods, along with specific case studies are presented. The 13 essays are: (1) "Prospects for a Better Understanding and Closer Cooperation between Anthropologists and Missionaries" (Louis J. Luzbetak); (2) "Anthropologists and Missionaries: Eternal Enemies or Colleagues in Disguise?" (Vinson H. Sutlive, Jr.); (3) "Parallaxis in Missiology: To Use or Abuse" (A. R. Tippett); (4) "Missionaries and the Perception of Evil" (Kenelm Burridge); (5) "Inculturation and Evangelisation: Realism or Romanticism?" (Gerald A. Arbuckle); (6) "A Missionary Philosophy of Development" (T. Wayne Dye); (7) "Developing Moralnets: Twenty-five Years of Culture Change among the Choco" (Jacob A. Loewen); (8) "Missionaries and Mourning: Continuity and Change in the Death Ceremonies of a Melanesian People" (John Barker); (9) "The Use of Missionary Documents in Ethnohistorical Research" (Darrell L. Whitman); (10) "Called for Life: The Literary Contribution of Edward M. Haymaker to an Ethnohistory of Protestant Missionary Ideology, Guatemala, 1887-1947" (David G. Scotchmer); (11) "Ethnology and Missionaries: The Case of the Anthropos Institute and Wilhelm Schmidt" (Ernest Brandewie); (12) "The Missionary as Cross-Cultural Educator" (Marvin K. Mayers); and (13) "Teaching Missionaires through Stories: The Anthropological Analysis of Indigenous Literature as an Aspect of a Cross-Cultural Orientation Program" (Miriam Adeney). (BZ)